2022
DOI: 10.3390/insects13010078
|View full text |Cite
|
Sign up to set email alerts
|

Thelytokous Reproduction of Onion Thrips, Thrips tabaci Lindeman 1889, Infesting Welsh Onion and Genetic Variation among Their Subpopulations

Abstract: Parthenogenesis is not uncommon in thrips. This asexual reproduction produces males (arrhenotokous) or female (thelytokous). Only females are found in the onion thrips (Thrips tabaci Lindeman 1889) infesting Welsh onion (Allium fistulosum) in several areas of Korea. To determine the reproduction mode of T. tabaci, thrips infesting Welsh onion were collected from different localities in Korea. Cytochrome oxidase I (COI) sequences were then assessed. Results showed that all test local populations had signature m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…We found that the main species of thrips that affects onion and its related species is Thrips tabaci , which is in agreement with previous studies [ 5 , 29 , 41 , 42 ]. Other thrips species such as Thrips palmi , Scirtothrips dorsalis , Frankliniella tenuicornis , Frankliniella intonsa , and Frankliniella occidentalis , were present at specific locations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the main species of thrips that affects onion and its related species is Thrips tabaci , which is in agreement with previous studies [ 5 , 29 , 41 , 42 ]. Other thrips species such as Thrips palmi , Scirtothrips dorsalis , Frankliniella tenuicornis , Frankliniella intonsa , and Frankliniella occidentalis , were present at specific locations.…”
Section: Discussionsupporting
confidence: 93%
“…Different levels of genetic diversity are reported for T . tabaci populations from different locations or years [ 24 , 41 , 43 , 60 ]. Based on our findings it is clear that the diversity of T .…”
Section: Discussionmentioning
confidence: 99%
“…Although all the three T. tabaci forms can coexist in onion and many other Allium host species. Khan et al (2022) reported that all the populations collected from Welsh onions in Korea consisted of thelytokous L2 type. It was also reported that the three T. tabaci forms differ in their virus transmission efficiency and that the T form is the most effective vector of TSWV, while L1 transmitted TSWV inefficiently (Chatzivassiliou et al 2002), while thelytokous populations (L2) did not transmit TSWV (Wijkamp et al 1995, Chatzivassilious et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of bacteria was reported to facilitate larval development and increase fecundity [ 28 ]. A similar type of bacteria might be localized in T. tabaci due to the similar life cycle and polyphagous feeding behavior, although T. tabaci , unlike F. occidentalis , is thelytokous (unfertilized diploid eggs becoming females) in the Korean population [ 29 ]. Like F. occidentalis , T. tabaci contained a dominant bacterial species identified as an Erwinia species, but its biochemical characteristics and 16S rDNA sequence differed from that of the bacteria present in F. occidentalis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%